Simulação do impacto de diferentes programas de dietas para suínos em crescimento e terminação - Camargo, Claudiele Aparecida dos Santos (2017)
Under practical breeding conditions, the pigs receive a sequence of diets during the growth and termination phase. The number of diets varies according to the nutritional and industrial aspects, where the most usual is to adopt programs containing between 3 and 5 diets. The length of time each diet is provided is based on the number of days it is assumed that the pigs will achieve a particular gain in body weight. However, there is variability in performance among individuals in a population and thus the use of a single diet program may not be the most appropriate both technically and economically. Thus, the objective of the study was to determine, through the simulation, the impact of diets programs and the variability among animals in lysine intake. The hypothesis of the study is that knowledge of variability allows the elaboration of diets that improve the utilization of resources. The study was performed simulating a population of castrated male pigs from 60 to 160 days of age. A population was generated by simulation from the Gompertz function in order to obtain different growth curves. A sample of the population represented by the light, medium and heavy pigs was taken. From the knowledge of the growth curve of the three categories was calculated the voluntary consumption and the metabolizable energy intake. Estimates for the calculation of lysine requirements were based on the factorial method. Three diets programs were established, the first containing three diets, the second four and third program with five diets. The lysine concentrations in the diets were based on the requirements of the heavy categorized pig and then applied to the light and medium animals. The comparison between the programs was performed considering the amount of lysine ingested and lysine excretion. In the simulation the amount of lysine ingested above the requirements was higher in the light animal followed by the medium and heavy and that the program containing 3 diets generated higher amounts of lysine than expected for the 3 categories of pigs. The lightweight swine ingested 1.1 pounds of lysine above what was needed to meet maintenance and production requirements. This value was 41 and 233% higher than those recorded with the medium and heavy pigs, respectively. The 3-diet program resulted in an intake of 0.81 kg of lysine above that required during the simulation period. Program 4, in turn, caused a consumption of 0.71 kg of lysine above the requirement, while program 5 the lysine ingested above the demand was 0.68 kg. The increase in the number of diets reduced the excess of ingested lysine, and this reduction will be greater the lower the population variability for the lysine requirement.